PATOGENISITAS ISOLAT BAKTERI Xanthomonas oryzae pv. oryzae DAN PEMANTAUAN PENYAKIT HAWAR DAUN BAKTERI PADA PADI GALUR ISOGENIK - Yadi Suryadi; Triny Suryani Kadir (BERITA BIOLOGI, 2017)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is an important rice disease due to its high intensity that and  the mereased durability of its resistant variety. This study was aimed  to determine the pathogenicity of Xoo isolates, which obtained from four regions/districts in West Java on three rice near isogenic lines (NILs) containing a single resistance (R) gene; and  to study reaction of rice NILs/ differential genotypes containing mixture of resistant genes to Xoo population under endemic areas. Out of 22 Xoo isolates have been collected and further determined by ELISA assay. Ten Xoo isolates were selected and inoculated to identify their pathogenicity on three NILs i.e., IRBB5 (xa5), IRBB7 (Xa7) and IRBB21 (Xa21). Pathogenicity test showed that most of isolates produced large lesion, and four virulence groups were identified. Phylogenetic analysis suggested that the dominant virulent isolates were widely distributed at several district in West Java. It was shown that 11 NILs exhibited high levels of resistant reaction to the predominant Xoo pathotypes in Cianjur, while 10 lines were susceptible. The single R gene (IRBB7, IRBB21 and Java14) exhibited lower BLB severity. The IRBB50, IRBB51, IRBB52, IRBB53 lines (carrying two R genes), IRBB56, IRBB57 (carrying three R genes); IRBB64 (carrying four R genes), and IRBB66 (carrying five R genes) showed lower severity and thus produced higher resistance to Xoo. This study may implied further work to deploy effective R genes against certain Xoo pathotypes in differ  region.